2002
DOI: 10.1515/znc-2002-5-608
|View full text |Cite
|
Sign up to set email alerts
|

Gas Chromatographic-Mass Spectrometry Study of the Essential Oils of Pimenta racemosa var. terebinthina and P. racemosa var. grisea

Abstract: The essential oil of the leaves of P. racemosa var. terebinthina and P. racemosa var. grisea were examined by GC and GC/MS. The major constituents were α-terpineol acetate (27%), α-terpineol (20%) and 4-methoxy eugenol (12.6%) for P.racemosa var. terebinthina and 4-methoxy-isoeugenol (75.2%) and 4-methoxy-eugenol (4.5%) for P. racemosa var. grisea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 0 publications
1
6
0
1
Order By: Relevance
“…[5][6]16 We analysed 17 and 20 volatile compounds from bay and red thyme oils, respectively, by GC-MS. Chemical components of red thyme and bay oils have been well studied. [7][8] Similar results were obtained in our analysis, although there was some difference in the ratios of chemicals. Ogihara and Takeda 17 had already reported that the essential oil content can vary markedly, depending on growing conditions.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…[5][6]16 We analysed 17 and 20 volatile compounds from bay and red thyme oils, respectively, by GC-MS. Chemical components of red thyme and bay oils have been well studied. [7][8] Similar results were obtained in our analysis, although there was some difference in the ratios of chemicals. Ogihara and Takeda 17 had already reported that the essential oil content can vary markedly, depending on growing conditions.…”
Section: Discussionsupporting
confidence: 89%
“…7 The genus Pimenta (family Myrtaceae) is widely represented in the Caribbean region and includes a large number of species and varieties which are traditionally used in local folk medicine. 8 In this study, we assessed the fungicidal activity of 26 commercially available plant essential oils and components derived from red thyme and bay essential oils against two phytopathogenic fungi to ¼nd new types of disease control alternatives.…”
Section: Introductionmentioning
confidence: 99%
“…The species of this genus are used in several countries including Barbados, Brazil, China, Cuba, Dominican Republic, England, Haití, India, Kerala, Mangalore, Mexico, Middle East, Taiwan, USA, and Venezuela [45][46][47][48][49][50][51][52][53][54][55][56], in various areas, whether to build agricultural tools, houses, or living fences because of the resistance of its wood against termites, industrially for the production of condiments, flavors, perfumes, and cosmetics, or in the treatment of various pathologies of traditional medicine such as fever, rheumatism, toothache, abdominal pain, pneumonia, colds, pectoral angina, diarrhea, incontinence, stroke, anti-inflammatory, and analgesic properties [10,12,15,[57][58][59]. Among pharmacological effects reported for different Pimenta species include anticancer, antidermatophytic, antihemorrhagic bleeding, anti-inflammatory, antimicrobial, antimutagenic, antinociceptive, antioxidant, antipyretic, central nervous system depressant, cobra venom, hypoglycemic, hypotensive, inhibitor of histone acetyl transferase enzyme, inhibitor of enzyme histidine carboxylase, and insect repellent [10,12,15,59].…”
Section: Genus Pimentamentioning
confidence: 99%
“…terebinthina essential oil presented α-terpineol acetate (37%), α-terpineol (20%) and methoxyeugenol (12.6%), as constituents, differently from P. racemosa var. grisea essential oil, which contains 4-methoxyisoeugenol (75.2%) and 4-methoxyeugenol (4.5%) (Garcia et al,2002).…”
Section: Chemical Composition Of Oilsmentioning
confidence: 99%